(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The uterus is a vital reproductive organ that is subjected to many benign and malignant diseases. Although many treatment options are available including medical and conservative surgical but hysterectomy remains the most common gynecological procedure performed worldwide. It is associated with many complications that increased mortality and morbidity. Aim: To evaluate the clinical indications of hysterectomy in Salahadeen Governorate. patients and Method: A prospective cross-sectional study was conducted in Salahadeen General Hospital /Gynecology and Obstetrics department during the period from 1st of December 2021 to 30th of June 2022, All the females who had hysterectomies during the study period were enrolled in the current study. The questionnaire was divided into four parts including sociodemographic characteristics, obstetrical characteristics, medical characteristics, and the main cause for hysterectomy. Results: A total of 57 patients were enrolled in the current study, patients with ages of 50-59consitituted more than half of the sample. More than half of the patients had overweight (56.1%), while 15.8% were obese. Most of the hysterectomies (91.2) were done electively, while the others were done due to emergency causes. Among elective causes, the fibroid was the most common cause of hysterectomy (25.0%), followed by adenomyosis and endometriosis (15.4% for each). Conclusion: Leiomyoma (Fibroid), adenomyosis, and endometriosis were the most common causes of hysterectomy. Most of the hysterectomies were done selectively rather than emergency hysterectomies.